Electronic structures and optical properties of Cu1-xAgxInTe2 (x = 0, 0.25, 0.5, 0.75 and 1) chalcopyrite compounds. (September 2018) - Zhong, Yuhan; Wang, Peida; Mei, Huayue; Jia, Zhenyuan; Cheng, Nanpu
Abstract: ABC2 chalcopyrite compounds are receiving increasing attention recently, and there are many researches of B-site or C-site doping. The current work mainly redresses the effects of A-site doping. The electronic structures and optical properties of Cu1- x Ag x InTe2 ( x  = 0, 0.25, 0.5, 0.75 and 1) compounds have been investigated by the first-principles approach based on density functional theory (DFT). Cu1- x Ag x InTe2 compounds are direct band-gap semiconductors, and the calculated band gaps are respectively 1.128, 1.086, 1.053, 1.029 and 1.01 eV, which coincide well with the experimental results. The Cu1- x Ag x InTe2 monocrystals with optical anisotropies have the potential applications in the fields of second harmonic generation and optical parametric oscillator. The polycrystalline Cu1- x Ag x InTe2 compounds have high absorption and reflection coefficients. Doping Ag atoms can further increase the photoconductivities of Cu1- x Ag x InTe2 compounds. Besides, CuInTe2, Cu0.25 Ag0.75 InTe2 and AgInTe2 compounds have high absorption capacities and photoconductivities in the visible light region, promising them great potentials to be photoelectric materials.